Studying Africa’s hydroclimate history over the last 2000 years - De Cort, Gijs (Afrika Focus, 2016)
Water-resource availability is one of the most important environmental factors on which Africa’s agricultural societies are reliant. However, our knowledge of the natural background variability of rainfall and drought over Africa is currently still inadequate to allow a full grasp of the relevant climate-dynamical mechanisms and guidance of much-needed forecasts of future trends. This report presents two new efforts to improve insights into how hydroclimate has varied throughout the continent over the past two millennia. Firstly, a thorough synthesis of data from instrumental measurements, historical accounts and natural climate archives resulted in an extensive review of Africa’s hydroclimate history. Secondly, the focus is narrowed to East Africa, where the sediments of hypersaline Lake Bogoria were used to reconstruct how a variable climate has driven large lake-level fluctuations over the last 1,300 years. Key words: paleoclimatology, natural climate archive, lake-level change, sedimentology, Lake Bogoria National Reserve